Assessment of signal processing methods for measuring the respiratory rate in the neonatal intensive care unit - Jorge, J; Villarroel, M; Chaichulee, S; Green, G; McCormick, K; Tarassenko, L (Institute of Electrical and Electronics Engineers, 2019)
Knowledge of the pathological instabilities in the breathing pattern can provide valuable insights into the cardiorespiratory status of the critically-ill infant as well as their maturation level. This paper is concerned with the measurement of respiratory rate (RR) in premature infants. We compare the rates estimated from (a) the chest impedance pneumogram, (b) the ECG-derived respiratory rhythms, and (c) the PPG-derived respiratory rhythms against those measured in the reference standard of breath detection provided by attending clinical staff during 165 manual breath counts. We demonstrate that accurate RR estimates can be produced from all sources for RR in the 40 - 80 bpm (breaths per min) range. We also conclude that the use of indirect methods based on the ECG or the PPG poses a fundamental challenge in this population due to their poor behaviour at fast breathing rates (upwards of 80 bpm).